A Philosophical Critique of Notarial Roles in Ensuring Legal Certainty in Land Relations: Kritik Filsafat terhadap Peran Notaris dalam Menjamin Kepastian Hukum dalam Hubungan Tanah - Nabila Putri Septiasari; Alisya Dania Karim; Keiza Febrina Amandita Putri; Dina Nada Kirana Ilmannavi’a (Academia Open, 2026)
General Background: Legal certainty in land transactions depends on authentic deeds and accountable public officers capable of protecting rights within the rule of law. Specific Background: Indonesian land administration remains vulnerable because formal-procedural reasoning dominates notarial practice, regulations governing Notaries and Land Deed Officials are fragmented, and supervision is divided between separate institutions. Knowledge Gap: Earlier studies largely addressed administrative harmonization or general theoretical solutions without developing a philosophical construction connecting legal certainty, social justice, and the constitutional social function of land. Aims: This study critiques the philosophical-juridical construction of Notary and Land Deed Official authority and formulates responsibilities supporting just land relations. It applies normative legal research through statutory and conceptual approaches, qualitative analysis, and deductive reasoning. Results: The prevailing positivist construction prioritizes documentary compliance while neglecting substantive justice, unequal bargaining positions, vulnerable groups, and the social function of land. Regulatory dualism and fragmented oversight also create ambiguity and accountability gaps. The proposed reformulation adopts a substantive-transformative paradigm through regulatory harmonization, stronger social-agrarian responsibility, integrated proactive supervision, and professional ethics oriented toward justice. Novelty: The study conceptualizes Notaries and Land Deed Officials as guardians of legal values and substantive justice rather than solely producers of formally valid deeds. Implications: Institutional reform should integrate oversight, clarify responsibility, strengthen preventive verification, and require officers to ensure informed and voluntary transactions while refusing deeds that materially disadvantage weaker parties or conflict with the social function of land. Highlights: Formal-procedural authority neglects social justice and the social function of land. Fragmented rules and divided supervision create accountability gaps during property transactions. PPAT duties require harmonized regulation, preventive oversight, and stronger responsibility toward vulnerable parties. Keywords: Legal Certainty, Land Governance Dynamics, Philosophical Critique, The Role of Notaries, The Agrarian Rule of Law State.